Structural variability and thermally-induced mesomorphisms in complexes of copper(II) with 4-halobenzoates, 2,2'-bipyridine and 4,4'-bis(dodecyl)-2,2'-bipyridine - Norbani Abdullah; Lailatun Nazirah Binti Ozair; Habibah Samsudin; Graham J. Tizzard; Simon J. Coles; Mohammad I. Mohamadin (Taylor & Francis Group, 2024)
Indexed by WOS/SCOPUS/ERA